NETosis: an emerging therapeutic target in renal diseases - Juha, Márk; Molnár, Adél; Jakus, Zoltán; Ledó, Nóra (Frontiers in Immunology, 2023)
Introduction Neutrophil extracellular traps (NETs) are web-like structures composed of nuclear and granular components. The primary role of NETS is to prevent the dissemination of microbes and facilitate their elimination. However, this process is accompanied by collateral proinflammatory adverse effects when the NET release becomes uncontrollable, or clearance is impaired. Although NET-induced organ damage is conducted primarily and indirectly via immune complexes and the subsequent release of cytokines, their direct effects on cells are also remarkable. NETosis plays a critical pathogenic role in several renal disorders, such as the early phase of acute tubular necrosis, anti-neutrophil cytoplasmic antibody-mediated renal vasculitis, lupus nephritis, thrombotic microangiopathies, anti-glomerular basement membrane disease, and diabetic nephropathy. Their substantial contribution in the course of these disorders makes them a desirable target in the therapeutic armamentarium. This article gives an in-depth review of the heterogeneous pathogenesis and physiological regulations of NETosis and its pivotal role in renal diseases. Based on the pathogenesis, the article also outlines the current therapeutic options and possible molecular targets in the treatment of NET-related renal disorders. Methods We carried out thorough literature research published in PubMed and Google Scholar, including a comprehensive review and analysis of the classification, pathomechanisms, and a broad spectrum of NET-related kidney disorders. Conclusions NETosis plays a pivotal role in certain renal diseases. It initiates and maintains inflammatory and autoimmune disorders, thus making it a desirable target for improving patient and renal outcomes. Better understanding and clinical translation of the pathogenesis are crucial aspects to treatment, for improving patient, and renal outcomes.